P 79 L5 radiculopathy induces sensory changes in the neighboring, unaffected S1 fibers. (May 2022) - Krämer, H.H.; Wassenberg, M.; Hansen, T.; Schänzer, A.; Kolodziej, M.; Geber, C.; Birklein, F.
Abstract : Background: Patients with radiculopathy frequently show sensory symptoms outside of the affected dermatome. We aimed to objectively describe sensory symptoms of the affected and the neighboring dermatome. Methods: We investigated the sensory profiles of 15 patients with a disc herniation affecting only the L5 root (7 women; age 56.9 ± 2.9 years) and 12 healthy controls (6 women; age 55.9 ± 2.7 years) within the bilateral L5 and S1 dermatomes using quantitative sensory test-ing (QST) according to the protocol of the German Research Network on Neuropathic Pain (DFNS). Results: L5 patients compared to controls: The cold detection (F=8.158; p=0.011) and warm detection (F=13.636; p=002) thresholds (WDT) were increased and the pressure pain threshold (PPT) was significantly decreased (F=5.664; p=0.029) in the affected L5 dermatome in NPP patients. The WDT were significantly increased (F=14.471; p=0.001) and PPT were decreased (F=4.835; p=0.042) in the S1 dermatome in the affected limb. Comparison between the affected and unaffected limb in L5 patients: Within the L5 dermatome, the WDT was significantly increased (p=0.021) and the PPT was significantly decreased in the affected leg (p=0.001). There was a tendency towards a lower mechanical detection threshold in the affected L5 dermatome (p=0.059). Within the S1 dermatome of the affected limb, the WDT is increased (p=0.039), the PPT is decreased (p=0.004) and the mechanical detection threshold is lower compared to the contralateral side (p=0.051). Conclusions: Exclusive L5 affection leads to changes in the sensory profile in the neighboring S1 fibers. The thermal hypaesthesia and the increased mechanical threshold can be explained by deafferentiation. L5 radiculopathy leads to sensitization of deep mechanoreceptors since pressure pain is decreased and heat pain remains unaltered.